Molecular Cloning, Expression, Purification and Immunological Characterization of Proteins Encoded by Regions of Difference Genes of Mycobacterium tuberculosis - Hanif, Shumaila Nida Muhammad; Al-Attiyah, Rajaa; Mustafa, Abu Salim (IntechOpen, 2011)
None